2016
DOI: 10.1108/cg-05-2015-0073
|View full text |Cite
|
Sign up to set email alerts
|

Does CEO duality give more influence over executive pay to the majority or minority shareholder? (A survey of Brazil)

Abstract: Purpose The purpose of this paper is to focus on comparing the influence of majority and minority shareholders on executive compensation under conditions of CEO duality, examining majority and minority shareholder influences by measuring their investment and return activity. The paper seeks to uncover how CEO duality changes the impact the two categories of shareholders have on executive compensation, especially in an emerging nation. Design/methodology/approach In total, 30 corporations out of the 70 corpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…The authors emphasized the positive relationship between the stock-based compensation and the price-to-equity ratio, suggesting that the long-term incentive played its role in creating long-term value. Abraham and Singh (2016) found a robust positive association between executive remuneration and the growth in the rates of return of controlling shareholders. Despite the low information quality that permeates emerging markets, they are not devoid of corporate governance mechanisms, which are considered crucial to reducing agency conflicts in these types of environments (Abudy et al, 2020).…”
Section: Relationship Between Executive Compensation and Firm Performancementioning
confidence: 94%
“…The authors emphasized the positive relationship between the stock-based compensation and the price-to-equity ratio, suggesting that the long-term incentive played its role in creating long-term value. Abraham and Singh (2016) found a robust positive association between executive remuneration and the growth in the rates of return of controlling shareholders. Despite the low information quality that permeates emerging markets, they are not devoid of corporate governance mechanisms, which are considered crucial to reducing agency conflicts in these types of environments (Abudy et al, 2020).…”
Section: Relationship Between Executive Compensation and Firm Performancementioning
confidence: 94%
“…These authors justified their results via the argument that the executive compensation in a family firm is a consequence of a family strategy to hire family members at the top of the control chain to maximize the family interest and to expropriate the company's wealth (Young et al, 2008;Faccio et al, 2001). A possible explanation for the rejection of hypothesis H4 can be related to the same explanation as hypothesis H3, that is, company pay culture and/or some other company characteristic ( BASEv.18, n.1, janeiro/março 2021Singh, 2016 and/or the Brazilian capital market characteristics and/or the organizational culture of the Brazilian public company. The comprehension of all these issues depends on future investigations, which may be conducted via qualitative or quantitative research methods or a combination.…”
Section: Analysis and Discussion Of The Resultsmentioning
confidence: 99%
“…Cohen and Lauterbach (2008) found that a CEO who belongs to the family receives significantly higher compensation than a CEO who does not belong to the controlling family group. For Abraham and Singh (2016), this behavior of executive pay is more rooted in the individual company pay culture or some other institutional company characteristic.…”
Section: Hypothesis 3: Ceteris Paribus There Is a Negative Relationship Between Variable Executive Compensation And Family Company Contromentioning
confidence: 99%
“…The control variables have been selected based on a detailed literature review. Prior scholars (Abraham and Singh, 2016;Benkraiem et al, 2017;Bova et al, 2015;Diasc et al, 2020;Mathew et al, 2016;Mathew et al, 2018;Pergola and Joseph, 2011;Petra and Dorata, 2008;Queiri et al, 2021) proved that the following control variables are the significant attributes for explaining corporate governance, executive compensation and their relation to risk: firm size, leverage, sector, institutional ownership, firm in loss, CEO's tenure, nationality, age and ownership, international board of directors (BOD), the board size, independent BOD, risk committee and CEO duality ( Because of the panel data set and the significant results of the Hausman test, fixed effect regression is the most appropriate technique for the models in this paper (Baltagi, 2012). Thus, the fixed firm-year effect regression analysis with robust standard errors was used to test the hypotheses.…”
Section: Model and Methodsmentioning
confidence: 99%